2020
DOI: 10.1002/adom.201901572
|View full text |Cite
|
Sign up to set email alerts
|

Lattice‐Enhanced Fano Resonances from Bound States in the Continuum Metasurfaces

Abstract: Fano resonances in metamaterials are known for their high quality (Q) factor and high sensitivity to external perturbations, which makes them attractive for sensors, lasers, and nonlinear and slow light devices. However, Fano resonances with higher Q factors obtained through structural optimization of individual resonators are accompanied by lower resonance intensity, thereby limiting the overall figure of merit (FoM) of the resonance. Here, a strategy for simultaneously enhancing the Q factor and FoM of Fano … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(47 citation statements)
references
References 56 publications
2
45
0
Order By: Relevance
“…On the other hand, recall the classical analogue of quantum electromagnetically‐induced transparency (EIT) has been widely explored in metasurfaces, where the three level system needed is typically replaced by mode coupling of two resonances of various kinds. [ 34–45 ] Nonetheless, even though, as mentioned above for BICs in general, metasurface quasi‐BICs with high Q‐factors have been widely investigated, [ 5,13,18,46–48 ] the use of BICs to achieve ultra‐narrow EIT has not been explored thus far.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, recall the classical analogue of quantum electromagnetically‐induced transparency (EIT) has been widely explored in metasurfaces, where the three level system needed is typically replaced by mode coupling of two resonances of various kinds. [ 34–45 ] Nonetheless, even though, as mentioned above for BICs in general, metasurface quasi‐BICs with high Q‐factors have been widely investigated, [ 5,13,18,46–48 ] the use of BICs to achieve ultra‐narrow EIT has not been explored thus far.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the trapped fields, lattice mode behaves as a dark mode existing in the metamaterials and its resonance frequency can be tuned by altering the periodic of meta‐atoms. [ 47–54 ] The lattice modes are observed as kinks or discontinuities in the transmission or reflection spectra of the metamaterials, and also referred to as diffractive modes or Woods anomalies. [ 47–54 ] The frequencies of the lattice modes for a square metamaterial structure can be evaluated as [ 48,52 ] fLM=cnPi2+j2where c is the speed of light in vacuum, n is the refractive index of the substrate, P is the lattice period, and ( i , j ) are non‐negative integers defining the order of the lattice mode.…”
Section: Resultsmentioning
confidence: 99%
“…[ 33 ] However, the toroidal resonance being the lower‐frequency spilt mode implies that coupling to the lattice mode requires a large period to fit the FOLM frequency, which would reduce the efficiency of devices. [ 47–54 ] To settle down this problem, we convert the gap‐coupling (capacitive‐coupling) to side‐coupling (inductive‐coupling) by flipping the arms of the two joint metallic loops, as shown in the inset of Figure 1a. The nature of toroidal resonance is generally identified by analyzing the opposite surface currents oscillating in the two loops.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its quality factor (Q-factor) is relatively low (Q < 10) [ 8 , 9 ] to achieve ultra-narrow-band resonance due to the excessively high ohmic loss of the metal, thus resulting in the impracticality of potential applications based on surface plasmon resonance. In recent years, a large number of studies have extensively conducted and deeply explored the optical nanodevices that excite ultra-high Q resonance lines to overcome this defect, mainly focusing on: the resonators of high refractive index dielectric materials related to bound or quasi-bound states in the continuum excite the Fano resonance of high Q-factor through strong coupling between modes [ 10 , 11 , 12 , 13 , 14 , 15 ], and the plasma lattice resonance and Fano resonance based on periodic structure [ 8 , 16 , 17 , 18 , 19 , 20 , 21 ]. Researchers found that the bound state (BIC) in the continuum can be confined completely, without any radiation, and reach a high Q-value (10 4 ) [ 10 , 11 , 12 , 13 ], and the all-dielectric material not only eliminates the ohmic loss, but also the radiation loss of the magnetic response is low, and devices that respond through multipole high-Q resonance in the near-infrared band have been rapidly developed [ 17 , 22 ].…”
Section: Introductionmentioning
confidence: 99%